Malaysia Assessment of the Start-Up Financing Ecosystem - Kuriakose, Smita (The World Bank, 2022)
In the context of the Coronavirus (COVID-19) pandemic and its impact on Malaysia's economy, the need to foster the emergence of an innovation-led economy has taken on increasing urgency. Public-sector involvement in the early-stage financing phase of the ecosystem is integral to crowding-in private investments, as seen by the impact of the establishment of government-sponsored venture capital (VC) funds in several small OECD countries, including Estonia and Finland. In turn, improved access to finance at the initial stages of a start-up and the crowding in of private capital will play a pivotal role in strengthening the entrepreneurship ecosystem. The government has devised a number of developmental roadmaps that emphasize the greater use of alternative forms of financing, such as VC and digital platform based models, including peer-to-peer financing (P2P) and equity crowdfunding (ECF). These strategies are an integral part of the government's strategies for maintaining growth as Malaysia achieves high-income nation status. This study aims to identify the financing gaps in Malaysia's start-up financing ecosystem and to propose specific policy levers to address the identified constraints on both the availability of and access to early-stage financing
Keywords: Capital Markets and Capital Flows; Coronavirus; COVID-19; Finance and Financial Sector Development; Financial Regulation and Supervision; Health Economics and Finance; Health, Nutrition and Population